1984
DOI: 10.1103/physrevb.30.803
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of strontium titanate

Abstract: We have employed the techniques of photoelectron spectroscopy {with tunable synchrotron radiation 30& h v& 100 eV) and inverse photoemission spectroscopy at h v=9.7 eV to study respectively the occupied and unoccupied electronic states of n-type SrTi03 doped with 1 at. /o Nb. Doped samples have the advantage that charging effects are avoided and hence a rather accurate determination of peak positions is possible. The total (occupied and empty) experimental density of states agrees with the calculated density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 31 publications
4
56
1
1
Order By: Relevance
“…3(c). Note that, if the ∼1.5-eV state was due to surface states, the intensity should scale, with decreasing bulk sensitivity (with increasing θ), to that of the 11-eV peak which originates from surface adsorbates [27]. This is clearly not the case as seen in Fig.…”
mentioning
confidence: 67%
“…3(c). Note that, if the ∼1.5-eV state was due to surface states, the intensity should scale, with decreasing bulk sensitivity (with increasing θ), to that of the 11-eV peak which originates from surface adsorbates [27]. This is clearly not the case as seen in Fig.…”
mentioning
confidence: 67%
“…Several methods are used for the removal of chlorophenols from the aqueous solutions such as adsorption, biodegradation, and advanced oxidation process [2]. SrTiO 3 (ST) is one of the important high band gap photoctalysts (band gap = 3.2 eV) [15]. It requires UV light to generate the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported theoretical calculations of the LDOS for d-band electrons have shown that the TiO 2 empty states occur at a lower energy than the SrO states 27,28 . Therefore, our assignment of the two different domains is consistent with these results.…”
mentioning
confidence: 98%